Characterization of Organic Soap Synthesized from Samia cynthia ricini Cocoon Extract and Its Antibacterial Potential - Rusdi, Hanumi Oktiyani; Wonorahardjo, Surjani; Kusumaningrum, Irma Kartika; Maisulah; Pribadi, Riza Agung; Putri, Adela Syiddah; Endang Ciptawati (Universitas Nusa Bangsa, 2024)
In a modern era that increasingly values health and sustainability, the demand for natural and environmentally friendly personal care products continues to grow. One response to this trend is the development of organic soaps produced from various natural ingredients. In this study, organic soap using Samia cynthia ricini silkworm cocoon extract has been synthesized. This study aims to assess the quality of organic soap synthesized from silk cocoon extract based on the Indonesian National Standard (SNI) quality criteria and its antibacterial potential. Silk cocoon soap is made from a mixture of silk cocoon extract with palm oil, coconut oil, olive oil, sodium hydroxide, and water. The quality measurements include organoleptic tests, pH, moisture content, total fat, insoluble substance in ethanol, and free fatty acids, based on SNI No. 4085: 2017 and 3532: 2016. Antibacterial testing is conducted by disc diffusion. The results showed that the synthesized silk cocoon soap has a yellowish-white color, a hard density, and no odor. The quality criteria of the soap meet the established standards, with a pH of 9.66, a water content of 11.47%, total fat of 75.00%, ethanol-insoluble substances of 0.52%, and free fatty acids of 1.58%. The soap also demonstrates antibacterial potential that describes by a larger diameter of the inhibitory area against Staphylococcus aureus bacteria.